A musculoskeletal modelling approach of the assessment of the risk of hamstring injuries in professional soccer players: a pilot study. Issue 1 (2nd January 2021) - Ménard, Mathieu; Sorel, Anthony; Boumpoutou, Rufin; Kulpa, Richard; Kerhervé, Hugo A.; Bideau, Benoit
ABSTRACT: Purpose: Evaluating and minimising the risk of hamstring injury remains complex as it lacks reliable field-testing. Kinematic analysis provides global external insights but fails to apprehend musculoskeletal loading. This study aimed to evaluate the association between hamstring function and prior injury using a novel functional test combined with a musculoskeletal approach. Methods: Twelve professional footballers, distributed in two groups (control or previously injured), performed a reactive functional test to one of four targets from a standing start and performed a knee and plantar extension on target. Joint kinematics served as input data of a musculoskeletal model, and joint angles and hamstring muscle lengths were calculated. Results: Biceps femoris long head (BFlh) was stretched to 150 ± 2% of initial length during the two conditions. Maximal BFlh length and time to stretch were significantly higher in the control group. Discussion: Kinematics and musculoskeletal parameters revealed that participants of the control group had higher maximal hip flexion, pelvis anterior tilt, and hip internal rotation than previously injured players. The combined approach of a hamstring functional test and musculoskeletal modelling gives new preliminary insights on the effect of previous history of hamstring injury on lower limb kinematics and BFlh muscle length.